Pengaruh Penerapan Hapa (Health Action Process Approach) Terhadap Peningkatan Kepatuhan Diet Pada Dm Tipe 2 Di Puskesmas Krian Sidoarjo - Dwi Indah Prasetia (2015)
Many people with type 2 of diabetes are unsuccessful to follow the recommended diet due to lack of motivation, memory and intention of DM patients to adhere proper diet of DM (Arsana et al, 2011). This study attempts to increase the motivation to improve intention of dietary adherence through the implementation of HAPA (Health Action Process Approach). The purpose of this study was to analyze the effect of HAPA (Health Action Process Approach) to increase dietary adherence in Diabetes type 2. This study was using a Quasy-Experiment. The population were patients with type 2 diabetes mellitus in Puskesmas Krian Sidoarjo in March-April 2015. Respondents in this study was 16 respondents. The independent variable was the implementation of HAPA. The dependent variable were self-efficacy, dietary adherence and blood sugar levels. The instruments in this study were questionnaires and blood sugar monitoring devices. Data were analyzed using statistical tests Wilcoxon Sign Rank Test and Mann Witney U test with significance α ≤ 0.05. The results of statistical test using Wilcoxon Sign Rank Test showed that the implementation of HAPA has an effect on self-efficacy in the treatment group (p=0.014), dietary adherence (p=0.025), blood sugar levels (p=0.009). Statistical test Mann Witney U test showed that there was an increase dietary adherence (p=0.002). In conclusion, the implementation of HAPA can improve dietary adherence in type 2 of diabetes mellitus. Future studies are expected to use more respondents and examine the whole variables contained in the HAPA theory.